Ուղղաձիգ լանդշաֆտների կանաչապատման հեռանկարները Երևանում - Գրիգորյան, Ա. Ա.; Խալաթյան, Ա. Ա.; Սահակյան, Մ. Ա.; Հովսեփյան, Ա. Գ. (ՀԱԱՀ հիմնադրամ)
Վերջին տարիներին Երևան քաղաքում գեոպլաստիկ փոփոխության ենթարկված մի շարք փողոցների և պողոտաների գեղազարդությունը բարելավելու նպատակով անհրաժեշտություն է առաջացել իրականացնել ուղղաձիգ կանաչապատում ։ Երևանի քաղաքապետարանի «Կանաչապատում և շրջակա միջավայրի պահպանություն » ՀՈԱԿ-ը 2022 թվականի աշնանը Մյասնիկյան պողոտայի սկզբնամասում՝ Սարալանջ տանող թունելի երկու կողմում (70 գծմ տարածքում) տնկել է բաղեղ, կամպսիս և կուսախաղող բուսատեսակներ, ինչի շնորհիվ ճանապարհամերձ տարածքներն ապագայում կվերածվեն կանաչ, տեղ-տեղ ծաղկող լանդշաֆտների։ В целях благоустройства ряда улиц и проспектов города Еревана, за последние годы претерпевших геопластические трансформации, возникла необходимость проведения вертикального озеленения. Осенью 2022 года ОНКО “Озеленение и защита окружающей среды” Ереванского городского муниципалитета в начале проспекта Мясникяна по обеим сторонам туннеля, ведущего в Сараландж (70 пог. м), были посажены декоративные растения – плющ, кампсис и девичий виноград, благодаря чему эти участки в будущем превратятся в зеленые, местами цветущие ландшафты. In recent years, urban green plantings have been significantly reduced in Yerevan; at the same time, due to geoplastic changes, scattered landscapes and rock walls have appeared, which significantly spoil the beautiful appearance of the capital. Therefore, there is a need to implement vertical landscaping. For vertical greening in residential areas, woody lianas are usually used, and in some cases, also grassy lianas and ampelous flowers. In order to improve and green the landscapes, we carried out ecological and biological research on a route basis, carried out appropriate geodetic measurements, and then prepared phytoplans and estimates for greening of some areas and landscapes. In the autumn of 2022, Yerevan Municipality “Greening and Environmental Protection” Community Non-Commercial Organization (“GEP” CNCO) has planted ivy, campsis, and creepers on both sides of the tunnel leading to Saralanj at the beginning of Myasnikyan Avenue (in an area of 70 square meters), due to which the roadside areas will turn into green, blooming landscapes. The selection of lianas was made according to the latter’s dendrocirculation indicators, decorative features and ecological flexibility. In the coming years, “Greening and Environmental Protection” CNCO will carry out vertical greening according to the above principle in similar landscapes of Myasnikyan Avenue, as well as Saralanj and Tsitsernakaberd highways (in the sections, that have undergone geoplastic change), turning the mentioned areas into green and blooming landscapes.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա